2010
DOI: 10.1088/0953-4075/43/16/165101
|View full text |Cite
|
Sign up to set email alerts
|

Electronic, magnetic and structural properties of neutral, cationic and anionic Fe2S2, Fe3S4and Fe4S4clusters

Abstract: This work reports density functional calculations of geometric, electronic and magnetic properties of freestanding iron-sulfur Fe 2 S 2 , Fe 3 S 4 and Fe 4 S 4 clusters which are the ones most frequently contained in proteins. We investigate neutral, anionic and cationic clusters using a method that employs linear combinations of atomic orbitals as basis sets, nonlocal norm-conserving pseudopotentials and a generalized gradient approximation to exchange and correlation. The results are discussed in connection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
(65 reference statements)
4
12
0
Order By: Relevance
“…The present calculations indicate that within each size, the Fe atom tends to form the largest probable number of bonds with O atoms, which is similar to iron sulfur clusters. 50 As discussed above, we nd that the ground state structures of (FeO) n 0/À/+ clusters are "ring structures" when n # 3, which is similar to the previous reported Fe n O m clusters. 51 When n $ 4, the ground state structures of (FeO) n 0/À/+ exhibit layer-like 3D congurations.…”
Section: Geometrical Structuressupporting
confidence: 89%
“…The present calculations indicate that within each size, the Fe atom tends to form the largest probable number of bonds with O atoms, which is similar to iron sulfur clusters. 50 As discussed above, we nd that the ground state structures of (FeO) n 0/À/+ clusters are "ring structures" when n # 3, which is similar to the previous reported Fe n O m clusters. 51 When n $ 4, the ground state structures of (FeO) n 0/À/+ exhibit layer-like 3D congurations.…”
Section: Geometrical Structuressupporting
confidence: 89%
“…The sulfur atom linking the three equivalent iron atoms is substantially polarized (0.35 μ B ), whereas the other three are less (3 × 0.13 μ B ). In our previous work, 18 using SIESTA, 40,41 we found a similar atomic structure with a different antiparallel spin arrangement (singlet state). This singlet state results at 0.18 eV from the ground state in the VASP calculation.…”
Section: Articlesupporting
confidence: 59%
“…As reported above, by using the SIESTA code 40,41 that employs Troullier−Martins pseudopotentials instead of PAWs for the core interactions and numerical pseudoatomic orbitals instead of plane waves as basis sets, our group found that these clusters conserve essentially the geometries they have inside core proteins. 18 To have the references of the host clusters, we reoptimized those structures with VASP. The cubic supercell throughout the calculations is chosen with an edge of 15 Å, being large enough to suppress any interaction between the periodically repeated images of the clusters.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the larger Fe-S clusters, as far as we known, there are few studies. Only the computational study on Fe 2 S clusters [33] have been performed, and the preliminary study on FeS À n (n = 1-6) [13] was carried out. In multicenter clusters, the electrons of iron atoms exhibit a weak magnetic coupling.…”
Section: Introductionmentioning
confidence: 99%